Potensi Dampak Hukum Atas Dilaksanakannya Joint Development Agreement dalam Penyelesaian Sengketa Blok Ambalat Antara Indonesia-Malaysia: Penelitian - Sinta Rosmawati Putri; Athina Kartika Sari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Ambalat Block dispute between Indonesia and Malaysia, which involves overlapping claims over hydrocarbon resources in the Sulawesi Sea, is a problem that requires an innovative and non-confrontational solution. The Joint Development Agreement (JDA) was proposed as the most pragmatic legal instrument to resolve this jurisdictional impasse. This study aims to analyze the legality of the implementation of JDA based on international law and the potential legal impact arising from its application in the Ambalat. The methodology used is normative legal research, focusing on the analysis of international conventions and state practices. The results of the study show that JDA has a solid legality, supported by Article 74(3) and Article 83(3) of the 1982 UNCLOS, as well as international customary norms. The JDA has the potential to turn disputes into profitable cooperation, strengthen bilateral law, and reduce the risk of international litigation. The success of the JDA relies heavily on the manifestation of genuine mutual will, a firm